Integrated Whole-Cell Biocatalysis for Trehalose Production from Maltose Using Permeabilized Pseudomonas monteilii Cells and Bioremoval of Byproduct - Trakarnpaiboon, Srisakul; Champreda, Verawat (Journal of microbiology and biotechnology, 2022)
Trehalose is a non-conventional sugar with potent applications in the food, healthcare and biopharma industries. In this study, trehalose was synthesized from maltose using whole-cell TBRC 1196 producing trehalose synthase (TreS) as the biocatalyst. The reaction condition was optimized using 1% Triton X-100 permeabilized cells. According to our central composite design (CCD) experiment, the optimal process was achieved at 35°C and pH 8.0 for 24 h, resulting in the maximum trehalose yield of 51.60 g/g after 12 h using an initial cell loading of 94 g/l. Scale-up production in a lab-scale bioreactor led to the final trehalose concentration of 51.91 g/l with a yield of 51.60 g/g and productivity of 4.37 g/l/h together with 8.24 g/l glucose as a byproduct. A one-pot process integrating trehalose production and byproduct bioremoval showed 53.35% trehalose yield from 107.4 g/l after 15 h by permeabilized cells. The residual maltose and glucose were subsequently removed by TBRC 12153, resulting in trehalose recovery of 99.23% with 24.85 g/l ethanol obtained as a co-product. The present work provides an integrated alternative process for trehalose production from maltose syrup in bio-industry.